Pengaruh Media Vidio Pembelajaran Terhadap Motivasi Belajar Siswa Di SMP Negeri 5 Dumai - Yadi Tristan; Ahmad Eddison; Supentri Supentri (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2022)
In this study, the media used by students for learning was video media. The question posed in this research is whether the learning video media at SMP Negeri 5 Dumai has an effect on students' learning motivation. This study uses statistical methods. The data collection instrument in this study used a questionnaire consisting of 15 questions. The sample in this study was 217 students who took part in learning using video media at SMP Negeri 5 Dumai. The learning rate of video media at SMP Negeri 5 Dumai is very good. This is because the instructional video media variable comes from the average percentage of respondents who answer very often is 41.95%, plus the average percentage of respondents who answer often is 54.3% which is the sum of 96.25%, where the range is 75.01%-100%. The students of SMP Negeri 5 Dumai are very motivated. This is because the influence of the instructional video media variable from the average percentage of respondents who answered very often was 44% plus the average percentage of respondents who answered often was 49.16%, so that it was added up with 93.16% results where the range was 75.01 %.-100%. The hypothesis is used to see the effect of the dependent variable, where the independent variable in this study is video media and the dependent variable is student learning motivation. Based on SPSS simple linear regression analysis, it can be seen that simple linear regression Y = 21.578+0.375 X. The results of the above formula can be changed to a constant 21578, namely the consistency value of the video media variable is 21578, and the regression coefficient X is 0.375 which indicates that the increase in the value of video media by 1% will increase learning motivation by 0.375. The positive coefficient indicates that the video media (X) has a positive effect on learning motivation (Y)